Switching from Twice-Daily Basal Insulin Injections to Once-Daily Insulin Degludec Injection for Basal-Bolus Insulin Regimen in Japanese Patients with Type 1 Diabetes: A Pilot Study - Yuka Tosaka; Akio Kanazawa; Fuki Ikeda; Mayu Iida; Junko Sato; Kazuhisa Matsumoto; Toyoyoshi Uchida; Yoshifumi Tamura; Takeshi Ogihara; Tomoya Mita; Tomoaki Shimizu; Hiromasa Goto; et al. (International Journal of Endocrinology)
The aim of this study was to investigate the efficacy of insulin degludec used for basal-bolus insulin regimen after switching from twice-daily basal insulin in Japanese patients with type 1 diabetes mellitus. The subjects were 22 type 1 diabetes patients treated with basal-bolus insulin regimen with twice-daily basal insulin. Basal insulin was switched to once-daily injection of insulin degludec with 10% dose reduction. HbA1c and fasting plasma glucose (FPG) were measured before and 12 weeks after switching. The frequency of hypoglycemic episodes, standard deviation (SD) of blood glucose, and mean of daily difference (MODD) were evaluated by continuous glucose monitoring (CGM) before and 4 weeks after switching. HbA1c and FPG before and 12 weeks after switching were comparable (HbA1c 8.5 ± 1.4 versus 8.7 ± 1.6%, P=0.28; FPG 203.2 ± 81.2 versus 206.5 ± 122.4 mg/dL, P=0.91). The frequency of hypoglycemia during nighttime was not significantly different at 4 weeks after switching (14.4 ± 17.0 versus 11.1 ± 15.0%, P=0.45). In addition, SD and MODD before and 4 weeks after switching were also comparable. In conclusion, glycemic control under once-daily insulin degludec injection was almost comparable to that under twice-daily basal insulin injections in Japanese type 1 diabetes patients. This study was registered with ID: UMIN000010474.